Open Educational Resource (OER): Achievements, Costs, and Challenges? - Nugraha, Hari Din; Kosasih, Deny Poniman; Kasda, Kasda; Malik, Syaeful; Kencanasari, R.A. Vesitara; Satibi, Ahmad; Firmansyah, Rian Oktariana; Fitriyanto, Noor Rian (INVOTEC, 2021)
The Open Educational Resource (OER) is a source of digital learning materials that can be accessed, used, and distributed by everyone and is copyright licensed. This study aims to conduct a systematic library review in investigating the impact of Open Educational Resource (OER) implementation on student learning outcomes, the impact of OER on costs for students and learning challenges using OER. The method used in this study is Systematic Literature Review (SLR). This paper presents a publication review paper (2015-2020) or the last 5 years on OER. The article search process uses search techniques using the keywords OER (Open Educational Resource), Open Educational, and MOOCs (Massive Open Online Course) on those from reputable article databases. The selected article is then sorted by the inclusion criteria process and the findings are synthesized to answer the problem formulation. The findings suggest that the effectiveness of OER learning and conventional textbooks has no significant differences, both of which have the same learning outcomes. In terms of costs, OER has an impact on saving students’ money. The challenge of learning in the future is the need for intensive support for teachers so that there is no longer a gap in teacher understanding related to OER. The role of librarians is required to collaborate in developing, modifying, and distributing OER, as well as in advocating to support the appropriate use of OER between teachers, students, and institutions. Research has implications as a strong foundation in designing and implementation strategies related to OER in education.